2016
DOI: 10.1039/c5ra22031a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of immobilized rubber on the non-linear viscoelasticity of filled silicone rubber with different interfacial interaction of silica

Abstract: The effect of temperature on Payne effect for spherical silica filled rubber combines characteristics of normally filled and pure rubber.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…The high G 0 level at lower strains and its rapid decline at higher strains is called Payne effect, [26][27][28] which is mainly caused by the existence of ller network under lower strains and its progressive collapse and destruction under higher strains. [29][30][31] As can be seen, with more addition of VMQ, G 0 of NR/VMQ increases, which indicates stronger structure of ller network.…”
Section: Filler Network and Dispersion Morphologymentioning
confidence: 87%
“…The high G 0 level at lower strains and its rapid decline at higher strains is called Payne effect, [26][27][28] which is mainly caused by the existence of ller network under lower strains and its progressive collapse and destruction under higher strains. [29][30][31] As can be seen, with more addition of VMQ, G 0 of NR/VMQ increases, which indicates stronger structure of ller network.…”
Section: Filler Network and Dispersion Morphologymentioning
confidence: 87%
“…Figure (a,b) exhibits the curves of storage modulus G ′ versus strain of the compounds, while Figure (c,d) shows the curves of vulcanizates. As is well‐known, the lower “Payne effect” indicates the higher uniformity of the filler dispersion and the weaker filler network structure in rubber matrix . Figure (a,b) and Supporting Information Table S2 showed that all the silica/NR compounds exhibited stronger “Payne effect” with increasing content of silica.…”
Section: Resultsmentioning
confidence: 63%
“…As is well-known, the lower "Payne effect" indicates the higher uniformity of the filler dispersion and the weaker filler network structure in rubber matrix. 7,37 Figure 5(a,b) and Supporting Information Table S2 showed that all the silica/NR compounds exhibited stronger "Payne effect" with increasing content of silica. While, the AS filled NR compounds illustrated much better filler dispersion, weaker filler network structures, and better filler-rubber interaction than those of PS ones.…”
Section: Effect Of Silica Contents and Types On Brcmentioning
confidence: 95%
“…It could also be observed that the 8 wt% specimen exhibited lower viscous properties in comparison to the 16 wt% and 12 wt% specimens, which was almost similar tos pure silicone rubber after 164 • C. Pure silicone rubber, however, displayed a different behaviour where the loss modulus increased up to 124 • C and then continued to decrease gradually with the heating temperature. The decrease trend of silicone rubber also showed that the performance of the silicone rubber in dissipating the energy was almost similar to those of 4 wt% and 8wt% specimens after 124 • C. This might due to the lower mobility of molecular chains of the silicone rubber as the internal friction in between the filler-filler and filler-matrix is lower as compared to the 12 wt% and 16 wt% specimens [63][64][65].…”
Section: Dynamic Mechanical Analysis (Dma)mentioning
confidence: 66%